(3GdJbSje hGdJHjjf aj Mce CehGd GdeSJaQbjfs - (3jMji Hf eMeO Hf GdhdjO GdTHdj GdHdfSj, CHh RcQjGs ((3CMeO Hf eMeO Hf CMeO Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO habfG Gddg hCjOce deG ajg QVi hZaQdfG s
(3BNQgG (B:s
(3eG jbQHfG ef BLQ KhGHg hjHGYOfi SNWg hYbGHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B315s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs